Full-scale photobioreactor for biotreatment of olive washing water: Structure and diversity of the microalgae-bacteria consortium. (August 2017) - Maza-Márquez, P.; González-Martínez, A.; Rodelas, B.; González-López, J.
Graphical abstract: Highlights: A full-scale photobioreactor (PBR) was applied for the removal of OWW pollutants. The microalgae-bacteria consortium in the PBR was studied by Illumina-sequencing. The selection of the DNA extraction method was crucial for community identification. OWW bioremediation relied on the Chlorophyta / Cyanobacteria / Proteobacteria interplay. Abstract: The performance of a full-scale photobioreactor (PBR) for the treatment of olive washing water (OWW) was evaluated under different HRTs (5–2 days). The system was able to treat up to 3926 L OWW day −1, and consisted of an activated-carbon pretreatment column and a tubular PBR unit (80 tubes, 98.17 L volume, 2-m height, 0.25 m diameter). PBR was an effective and environmentally friendly method for the removal of phenols, COD, BOD5, turbidity and color from OWW (average efficiencies 94.84 ± 0.55%, 85.86 ± 1.24%, 99.12 ± 0.17%, 95.86 ± 0.98% and 87.24 ± 0.91%, respectively). The diversity of total bacteria and microalgae in the PBR was analyzed using Illumina-sequencing, evaluating the efficiency of two DNA extraction methods. A stable microalgae-bacteria consortium was developed throughout the whole experimentation period, regardless of changes in HRT, temperature or solar radiation. MDS analyses revealed that the interplay between green algae ( Sphaeropleales ), cyanobacteria ( Hapalosiphon ) and Proteobacteria ( Rhodopseudomonas, Azotobacter ) played important roles in OWW bioremediation.